2012
DOI: 10.3102/0034654312464909
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing the Evidence on Classroom Goal Structures in Middle and Secondary Schools

Abstract: This meta-analysis and narrative review synthesizes the literature on classroom goal structures and their relationships with student outcomes, focusing additionally on the ways in which these constructs are operationalized across research studies. Specifically, this study evaluates the relationships between students’ perceptions of mastery and performance classroom goal structures and secondarily of teacher support as related to academic achievement and motivational and psychological outcomes. The findings doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
12

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(49 citation statements)
references
References 117 publications
2
23
0
12
Order By: Relevance
“…Further from our more restrictive prediction (hypothesis 4), CAFSap promoted the adoption of different types of goals, not only the matching (Sap), and all had a proximal influence in the motivational results. For its part, results of the relation CAFOap -Oap were convergent with previous studies who found that performance-approach CAF leads to the adoption of performance-approach goals (Schwinger, & Stiensmeier-Pelster, 2011;Urdan, 2004), and those who emphasize the maladaptive role of both CAF and personal performance-approach goals (Anderman, Cupp, & Lane, 2009;Givens-Rolland, 2012;Kaplan, Gheen, & Midgley, 2002;Lau, & Nie, 2008;Murdock, Hale, & Weber, 2001).…”
Section: Discussionsupporting
confidence: 77%
“…Further from our more restrictive prediction (hypothesis 4), CAFSap promoted the adoption of different types of goals, not only the matching (Sap), and all had a proximal influence in the motivational results. For its part, results of the relation CAFOap -Oap were convergent with previous studies who found that performance-approach CAF leads to the adoption of performance-approach goals (Schwinger, & Stiensmeier-Pelster, 2011;Urdan, 2004), and those who emphasize the maladaptive role of both CAF and personal performance-approach goals (Anderman, Cupp, & Lane, 2009;Givens-Rolland, 2012;Kaplan, Gheen, & Midgley, 2002;Lau, & Nie, 2008;Murdock, Hale, & Weber, 2001).…”
Section: Discussionsupporting
confidence: 77%
“…Educational interest, however, involves a focus on the pedagogical handling of students and their individual development. This focus probably facilitates mastery-oriented practices because these are beneficial for students' competence perceptions and motivation (Givens Rolland, 2012). In contrast, cognitively activating practices are more closely associated with students' cognitive learning processes and therefore may depend less strongly on educational interest.…”
Section: Teacher Interestsmentioning
confidence: 91%
“…There is ample evidence that mastery goal structures in the classroom predict students' mastery goals, whereas performance goal structures predict students' performance (or ability) goals (Meece, Anderman, & Anderman, 2006;Urdan, 2010;Urdan & Schoenfelder, 2006). Moreover, mastery goal structures contribute positively to students' competence beliefs, motivational engagement (e.g., effort), strategy use, and academic achievement (Givens Rolland, 2012;Urdan, 2010;Wolters, 2004). In contrast, performance goal structures do not or negatively (depending on the grade level) contribute to these outcome measures (see also Meece et al, 2006).…”
Section: Teacher Mastery Goalsmentioning
confidence: 94%
See 1 more Smart Citation
“…Negatív irányú az összefüggése vagy nem függ össze az elsajátítási célstruktúra olyan kedvezőtlen kimenetekkel, mint a negatív érzelmek, a nem adaptív segítségkérés, a tanult tehetetlenség vagy a csalás. A viszonyító célstruktúra észlelése az osztályteremben általában kedvezőtlen kimenetekhez kapcsolódik, úgy mint alacsonyabb teljesítmény, csalás, tanult tehetetlenség, kitartás hiánya (l. Kaplan és Maehr, 2007;Givens Rolland, 2012). Az elsajátítási célstruktúra általában erősebb kapcsolatban áll a tanulói kimenetekkel, mint a viszonyító célstruktúra.…”
Section: Célstruktúrákunclassified